Outcomes, health-care resources use, and costs of endoscopic removal of metallic airway stents - Alazemi, Saleh; Lunn, William; Majid, Adnan; Berkowitz, David; Michaud, Gaetane; Feller-Kopman, David; Herth, Felix; Ernst, Armin (Chest, 2010)
Background - The use of self-expandable metallic airway stents (SEMAS) for airway compromise may be associated with significant complications requiring their removal/replacement. The aim of this study is to describe the complications, health-care resources use (HRU), and costs associated with endoscopic removal of SEMAS. - Methods - A retrospective analysis of patients who underwent endoscopic removal of SEMAS during a 10-year period (January 2000-August 2009) was performed. HRU was analyzed in terms of the number of endoscopic procedures, hospital and ICU stay, need for mechanical ventilation and airway restenting, and estimation of respective hospital costs. - Results - Fifty-five SEMAS were removed from 46 patients with a mean age of 58.6 ± 15.8 years. Eighty percent of the stents were placed for benign airway disorders with an average stent in situ duration of 292 days. The median number of removal and total procedures during each encounter was one and two, respectively. Patients required hospitalization and ICU admission in 78% and 39% of the encounters with a median length of stay of 3.5 and 0 days, respectively. The estimated median total cost per encounter to remove the stents was $10,700, ranging from $3,700 to $69,800. The measured outcomes were statistically significantly better when in situ stent duration was ≤ 30 days (P < .05). - Conclusions - Endoscopic removal of SEMAS is feasible; however, it is associated with significant complications, HRU, and costs. The use of SEMAS should be restricted to a well-selected patient population and should be planned by a team experienced with this type of therapeutic strategy.